2021
DOI: 10.1371/journal.pone.0253492
|View full text |Cite
|
Sign up to set email alerts
|

Angiotensin-converting enzyme inhibitors versus angiotensin II receptor blockers on insulin sensitivity in hypertensive patients: A meta-analysis of randomized controlled trials

Abstract: Introduction This meta-analysis aimed to summarize the available evidence to compare angiotensin-converting enzyme (ACE) inhibitors with angiotensin II receptor blockers (ARBs) on improving insulin sensitivity in hypertensive patients. Methods Randomized controlled trials (RCTs) comparing ACE inhibitors versus ARBs published with outcomes on homeostasis model assessment of IR (HOMA-IR), glucose infusion rate (GIR), the quantitative insulin sensitivity check index (QUICKI), insulin sensitivity index (ISI) com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…Similarly, in a meta-analysis (n=1,015), ACEi were superior on HOMA-IR improvement vs. ARBs in the long-term intervention subgroup of patients (mean difference: 0.41, CI: [0.06, 0.76]; p=0.022) 53 .…”
Section: Arbs Vs Aceimentioning
confidence: 88%
“…Similarly, in a meta-analysis (n=1,015), ACEi were superior on HOMA-IR improvement vs. ARBs in the long-term intervention subgroup of patients (mean difference: 0.41, CI: [0.06, 0.76]; p=0.022) 53 .…”
Section: Arbs Vs Aceimentioning
confidence: 88%
“…Moreover, RA patients also took glucocorticoids significantly more frequently, above all if non-diabetic. As is known, chronic glucocorticoid use may increase the risk of developing both hypertension and diabetes [ 45 ], and some anti-hypertensive agents can also improve glucose metabolism [ 46 , 47 ]. Comorbidities may have an impact on how patients with RA are managed and eventually their quality of life, which emphasizes the value of a customized therapeutic approach [ 48 , 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…In reflection of high mortality and morbidity, ACE inhibitors were superior to ARBs in patients with high blood pressure and type 2 diabetes mellitus [10]. In another meta-analysis published in PLoS One, it was shown that ACE inhibitors give rise to a more potent improvement of the homeostasis model assessment of insulin resistance (HOMA-IR) in comparison with ARBs among the long-term intervention and high blood pressure patients with diabetes mellitus subgroup [11]. Although ARBs have a good safety profile, ACE inhibitors have additional benefits when it comes to the management of diabetic patients with high blood pressure.…”
Section: Introductionmentioning
confidence: 99%